Diagnosis, significance, and management of ventricular thrombi in patients referred for VT ablation. (28th July 2021) - Beavers, David L.; Ghannam, Michael; Liang, Jackson; Cochet, Hubert; Attili, Anil; Sharaf‐Dabbagh, Ghaith; Latchamsetty, Rakesh; Jongnarangsin, Krit; Morady, Fred; Bogun, Frank
Abstract: Introduction: In patients with structural heart disease presenting with ventricular tachycardia (VT), detection of ventricular thrombi and subsequent management can be challenging. This study aimed to assess the value of multimodality imaging with cardiac magnetic resonance imaging (CMR), contrast‐enhanced transthoracic echocardiography (TTE), and computed tomography (CT) for thrombus detection as well as a management algorithm geared towards anticoagulation and deferred ablation for patients referred for VT ablation. Methods and results: A total of 154 consecutive patients referred for VT ablation underwent preprocedural multimodality imaging with CMR, CT, and TTE. In 9 patients (6%) a new ventricular thrombus was detected and anticoagulation was initiated. Thrombi were detected by CMR in nine patients, by CT in seven patients, and by TTE in two patients. Five patients eventually underwent endocardial VT ablation procedures 6.0 ± 2.0 months after initiation of anticoagulation with one patient also requiring an epicardial approach. Two patients died while on anticoagulation, unrelated to ventricular arrhythmia. Four of five patients were rendered non‐inducible and no testing was performed in 1/5 patients. Areas containing left ventricular thrombi were non‐excitable with pacing. Six of thirty‐two inducible VTs were mapped in close vicinity of ventricular thrombi. No clinical embolic events occurred during the ablation procedures. Conclusions: Ventricular thrombus was detected in 6% of consecutive patients with structural heart disease undergoing VT ablation. CMR was the most sensitive modality, while contrast‐enhanced TTE failed to detect the majority of thrombi. Anticoagulation followed by ablation can be safely and successfully performed in patients with ventricular thrombi.